2014
DOI: 10.1111/jdv.12806
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance confocal microscopy: non‐invasive distinction between actinic keratosis and squamous cell carcinoma

Abstract: This study revealed specific RCM features that can distinguish between AK and SCC, stimulating further prospective, large cohort research in this field. This will result in correct, efficient and adequate diagnosis and treatment of clinically difficult to distinguish AK and SCC lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 48 publications
5
51
0
1
Order By: Relevance
“…36 While there is some overlap in the RCM features of SCCs and actinic keratoses, a disarranged epidermal pattern at the spinous-granular layer and the presence of neoplastic aggregates in the dermis are highly suggestive of SCC (Fig 9). 37 Notably, imaging of …”
Section: Reflectance Confocal Microscopy Features Of Malignant Cutanementioning
confidence: 99%
“…36 While there is some overlap in the RCM features of SCCs and actinic keratoses, a disarranged epidermal pattern at the spinous-granular layer and the presence of neoplastic aggregates in the dermis are highly suggestive of SCC (Fig 9). 37 Notably, imaging of …”
Section: Reflectance Confocal Microscopy Features Of Malignant Cutanementioning
confidence: 99%
“…Contrast enhancement using dye (5% acetic acid) and cross‐polarization imaging has been proposed to address this challenge for nonmelanoma skin cancer . A recent study imaging 30 lesions in vivo (6 cutaneous SCCs, 24 actinic keratoses) demonstrated the utility of confocal microscopy to noninvasively distinguish between cutaneous SCC and actinic keratosis with 88.5% accuracy . However, poor interobserver agreement in all but the most experienced confocal microscopy operators was reported.…”
Section: Optical Imaging In Margin Assessmentmentioning
confidence: 99%
“…Atypical honeycomb/ a disarranged pattern 100% [40][41][42] Round nucleated cells at the spinous-Granular Layer 50-65% 40,41 Round vessels in the dermis 39-100% 40,41 Multiphoton tomography…”
Section: Figurementioning
confidence: 99%